Comparison of codependency characteristics of individuals with and without dependent relatives in terms of defense mechanisms, family functionality and attachment styles - Özüak-Tunca, Işıl; Özen-Akın, Gaye; Dayi, Ali (Journal of Dependence, 2024)
Objective: This study aimed to identify both the shared and distinct aspects of the codependency characteristics of individuals with (clinical group, n=56) and without dependent relatives (non-clinical group, n=59) by comparing them in terms of personal (defensemechanisms), domestic (family-functionality), and relational (attachment-styles) contexts. Method: Codependency Assessment Tool (CODAT), Defense Styles Questionnaire 40 (DSQ-40), Family Assessment Device (FAD), and Relationship Scales Questionnaire (RSQ) were used as data collection tools. Results: The clinical group scored statistically significantly higher on CODAT (other focus/self-neglect, low-self-worth, family-of-origin-issues subscales and total), DSQ-40 (immature-defenses subscale), FAD (failure in problem-solving, communication, roledistribution, affective-responsiveness, affective-involvement, general-functioning subscales and total), RSQ (preoccupied-attachment subscale) than the non-clinical group. The non-clinical group scored significantly higher on the mature-defenses subscale than the clinical group. Immature-defenses, failure in problem-solving and preoccupied-attachment predicted codependency in the clinical group whereas in the non-clinical group, immature-defenses and unhealthy-communication were significant predictors of codependency. Conclusion: Codependency characteristics differ among individuals with and without dependent family members. As immature defenses predicted codependency in both groups, the use of this defense mechanism may be a fundamental feature of codependency.